2021
DOI: 10.1111/nph.17160
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomics reveals dynamic genome evolution in host specialist ectomycorrhizal fungi

Abstract: Summary While there has been significant progress characterizing the ‘symbiotic toolkit’ of ectomycorrhizal (ECM) fungi, how host specificity may be encoded into ECM fungal genomes remains poorly understood. We conducted a comparative genomic analysis of ECM fungal host specialists and generalists, focusing on the specialist genus Suillus. Global analyses of genome dynamics across 46 species were assessed, along with targeted analyses of three classes of molecules previously identified as important determina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
57
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 54 publications
(65 citation statements)
references
References 178 publications
8
57
0
Order By: Relevance
“…The evolution of ECM genomes within a single lineage has been investigated for the Amanitaceae, which showed a rapid expansion and contraction of functionally relevant genes early in the evolution of the ECM habit (Hess et al ., 2018). Another study focusing on the Pinaceae‐associated genus Suillus found dynamic gene evolution within the lineage, with secondary metabolites linked to host specificity (Lofgren et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The evolution of ECM genomes within a single lineage has been investigated for the Amanitaceae, which showed a rapid expansion and contraction of functionally relevant genes early in the evolution of the ECM habit (Hess et al ., 2018). Another study focusing on the Pinaceae‐associated genus Suillus found dynamic gene evolution within the lineage, with secondary metabolites linked to host specificity (Lofgren et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Functional traitssuch as gene copy numbers for PCWDEs, N and phosphate acquisition pathways, MiSSPs, and TEswithin a fungal family across functional guilds (e.g. saprotrophs vs symbiotrophs) have been investigated within the Amanitaceae, Endogonaceae, Russulaceae, Suillaceae, and Tuberaceae (Hess et al, 2018;Murat et al, 2018;Chang et al, 2019;Lofgren et al, 2021;Looney et al, 2021). These studies have shown that the aforementioned hallmarks of the ectomycorrhizal ecology are recapitulated at the family level, although idiosyncrasies have been identified in each of these fungal families, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…How host specificity may be encoded into EcM fungal genomes and driven by gene expression remains poorly understood. In their global analysis of gene family dynamics for 23 Suillus species, Lofgren et al (2021) found that host specialist Suillus genomes encode numerous rapidly evolving gene families, representing both gene family expansions and contractions. Gene families coding for terpene- and non-ribosomal peptide synthetase-like secondary metabolite clusters, known to play a role in the structuring of host specificity relationships for fungi, are significantly enriched in Suillus species.…”
Section: Introductionmentioning
confidence: 99%